Confronting the COVID-19 By Digital Economy Utilization in MSMEs - Dhian Adhitya; Birgitta Dian Saraswati; Sotya Fevriera; Virgiana Nugransih Siwi; Yustinus Wahyudi (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2022)
This study aimed to identify the effect of applying digital economy in the framework for improving MSMEs’ strength and resilience in Salatiga City before and after the COVID-19 pandemic. This research used 134 samples representing all small and medium enterprises in Salatiga City. The data focused in this research related to the application of the digital economy by business actors in Salatiga City. The analytical techniques of this research included descriptive statistics and a multiple linear regression model estimated by ordinary least squares (OLS). The result of this research indicated that the application of the digital economy in the framework for improving MSMEs’ strength and resilience amidst the COVID-19 pandemic was not proven in this study. The variables of the digital economy and total length of business did not significantly affect the turnover of the MSME actors in Salatiga City. Meanwhile, the labor variable proved to have a positive and significant effect on the turnover of the MSME actors in Salatiga City. However, the service business sector has been shown to negatively and significantly impact the turnover of MSME actors. MSMEs engaged in the service business sector tended to have lower turnover than MSMEs engaged in the trade business sector.